A fast-evolving luminous transient discovered by K2/Kepler. (April 2018) - Rest, A.; Garnavich, P.; Khatami, D.; Kasen, D.; Tucker, B.; Shaya, E.; Olling, R.; Mushotzky, R.; Zenteno, A.; Margheim, S.; Strampelli, G.; James, D.; et al.
Abstract For decades, optical time-domain searches have been tuned to find ordinary supernovae, which rise and fall in brightness over a period of weeks. Recently, supernova searches have improved their cadences and a handful of fast-evolving luminous transients have been identified1–5 . These have peak luminosities comparable to type Ia supernovae, but rise to maximum in less than ten days and fade from view in less than one month. Here we present the most extreme example of this class of object thus far: KSN 2015K, with a rise time of only 2.2 days and a time above half-maximum of only 6.8 days. We show that, unlike type Ia supernovae, the light curve of KSN 2015K was not powered by the decay of radioactive elements. We further argue that it is unlikely that it was powered by continuing energy deposition from a central remnant (a magnetar or black hole). Using numerical radiation hydrodynamical models, we show that the light curve of KSN 2015K is well fitted by a model where the supernova runs into external material presumably expelled in a pre-supernova mass-loss episode. The rapid rise of KSN 2015K therefore probes the venting of photons when a hypersonic shock wave breaks out of a dense extended medium. A fast-evolving luminous transient (FELT) has been detected with a rise time to peak luminosity of only 2.2 days. This implies that the light-curve of this FELT cannot be powered by the decay of radioactive elements, as with type Ia supernovae.